The Impact of Environmental Knowledge and Green Brand Image on Green Repurchase Intention by Mediation of Attitude - Aisyah, Nugrahanti Khairani; Shihab, Muchsin Saggaff (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
This paper seeks to examine the role of attitude towards green product on the relationship between environmental knowledge and green brand image for green repurchase intention. The research method used is quantitative descriptive research with Structural Equation Modeling (SEM) approach. The population in this study was collected from 125 respondents’ consumers who have used environmentally friendly slow fashion products (Fjallraven, Converse dan Timberland) in Jabodetabek – Indonesia. Findings – It was found that environmental knowledge has a significant positive effect on green repurchase intention. Green brand image has an insignificant positive effect on green repurchase intention. Furthermore, variable of attitude towards green product and green brand image has a positive and significant effect on green repurchase intention through attitude towards green product.